(untitled) (IJOVTECH, 2026)
Several studies have found that vegetables are an essential part of plants contributing significantly to health and well-being. Vegetables are a plentiful source of nutrients and dietary fiber, both of which are essential for good health. However, growing evidence suggests that vegetable consumption is linked to several pathogenic organisms of public health concern. The present study was conducted to identify and isolate the bacterial composition of fluted pumpkin, bitter leaf, and scent leaf frequently sold at various markets in Ikwo, Ebonyi State. The standard microbiological procedure evaluated the bacteria using the serial dilution method. The result showed that the samples collected from different vendors contained various microbial loads. It was indicated that the bitter leaf had a higher bacteria load, while the pumpkin leaf held a moderate load of bacteria, and the scent leaf recorded the lowest plate count. Most importantly, the primary bacteria isolated were Pseudomonas species, Bacillus, Erwinia spp, and Streptococcus. Accordingly, the paper concluded that most vegetables obtained from rural markets are likely to be loaded with numerous bacteria beyond the acceptable recommendations of the world health organization. The study has implications for health maintenance and well-being.